Adults with Childhood Illnesses : Considerations for Practice. - Bricker, J. Timothy (Health, medicine, and human development., 2011)
Just a few decades ago, children born with significant congenital anomalies or genetic and metabolic diseases perished at an early age and very few survived into their teens and even less into adulthood. Congenital heart disease, major errors in metabolism, cancer, cystic fibrosis and many other major diseases were fatal. Because of that many physicians in adult primary care did not have the opportunity to see patients with these problems and thus unable to learn how to care for them. This book provides a resource for all health care providers in order to help with caring for such adult patien.